Ovule cell wall composition is a maternal determinant of grain size in barley - Xiujuan Yang; Laura G. Wilkinson; Matthew K. Aubert; Kelly Houston; Neil J. Shirley; Matthew R. Tucker (2023)
In cereal species, grain size is influenced by growth of the ovule integuments (seed coat), the spikelet hull (lemma and palea) and the filial endosperm. Whether a highly conserved ovule tissue, the nucellus, has any impact on grain size has remained unclear. Immunolabelling revealed that the barley nucellus comprises two distinct cell types that differ in terms of cell wall homogalacturonan (HG) accumulation. Transcriptional profiling of the nucellus identified two pectin methylesterase (PME) genes, OVULE PECTIN MODIFIER 1 (OPM1) and OPM2, which are expressed in the unfertilized ovule but absent from the seed. Ovules from an opm1 opm2 mutant and plants expressing an ovule-specific pectin methylesterase inhibitor (PMEI), exhibit reduced HG accumulation. This results in changes to ovule cell size and shape and ovules that are longer than wild-type (WT) controls. At grain maturity, this is manifested as significantly longer grain. These findings indicate that cell wall composition during ovule development acts to limit ovule and seed growth. The investigation of ovule PME and PMEI activity reveals an unexpected role of maternal tissues in controlling grain growth before fertilization, one that has been lacking from models exploring improvements in grain size.